Multiple UAV coalition formation for multiple tasks - Sujit Baliyarasimhuni (2009)
In a search and prosecute mission, multiple heterogeneous unmanned aerial vehiclesUAVs that carry different resources need to perform the classify, prosecute and battledamage assessment (BDA) tasks on targets sequentially. Depending on the target resource requirement,it may be necessary to deploy a coalition of UAVs to perform the action. In thispaper, we propose coalition formation algorithms that have low computational overhead todetermine coalitions for the prosecute and the BDA tasks. We also develop a simultaneousstrike mechanism based on Dubins curves for the UAVs to prosecute the target simultaneously.Simulation results are presented to show how the algorithms work with theoretical results.